Forced Displacement Associated Adjustment Issues among the Middle-Aged Population: A Comparative Study: Understanding the Impact of Forced Displacement on Middle-aged Population's Adjustment Issues (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Development induced displacement often leads to maladjustment and decline of livelihood among the affected communities. The purpose of the present research is to study the impact of forced displacement and associated adjustment issues among middle-aged population in Shivamogga district located in the state of Karnataka. The sample consisted of 120 respondents, including 60 displaced and 60 non-displaced participants between 45-65 years. Semi-structured interview and Shamshad-Jasbir old age adjustment inventory was administered and results were analyzed. The study showed that there is a statistically significant lower mean in total adjustment score among the displaced people, suggesting poor adjustment to forced displacement. Importantly, the results of the study indicated that displaced population had significantly poor social and emotional adjustment, relative to the non-displaced people. We conclude that resettlement and rehabilitation programs should work together along with the local community, instead of providing mere compensation to ensure positive social and emotional outcomes for displaced populations.